Cultura do consumo, cidadania e movimentos sociais - Gisela Taschner (Ciências Sociais Unisinos)
Consumption and citizenship are considered by most scholars as belonging to distinct fi elds, and, for a long time, they were theorized separately. In cases which they were approached jointly, even from different theoretical perspectives, the relations between consumption and citizenship emphasized were of opposition, antagonism, and mutual exclusion. In this sense, this article aims to explore the relation between consumption and citizenship from other angles. The main argument is that their relation is multifaceted, and therefore it is more complex than what has been evidenced in most studies. In order to develop this argument, some key-moments in the formation of consumer culture, and the social movements for consumer protection are considered. Furthermore, it is analyzed the convergence among several kinds of political activism, which encompasses consumers¿ social movements, a trend which started by the end of the twentieth century and seems to be gaining momentum. The results found derive from empirical data collected in 1994 in a comparative study about the history of consumer protection, part of which has been recently updated.